Social–emotional processing in nonverbal individuals with Angelman syndrome: evidence from brain responses to known and novel names. Issue 3 (23rd November 2018) - Key, A. P.; Jones, D.
Abstract: Background: The combination of intellectual, communicative and motor deficits limits the use of standardised behavioural assessments in individuals with Angelman syndrome (AS). The current study aimed to objectively evaluate the extent of social–emotional processing in AS using auditory event‐related potentials (ERPs) during passive exposure to spoken stimuli. Methods: Auditory ERP responses were recorded in 13 nonverbal individuals with the deletion subtype of AS, age 4–45 years, during the name recognition paradigm, in which their own names and names of close others (relative or friend) were presented among novel names. No behavioural responses were required. Results: Contrary to findings in typical children and adults, there was no significant evidence of differential neural response to known vs. novel names in participants with AS. Nevertheless, greater amplitude differences between known and unknown names demonstrated the predicted association with better interpersonal relationships and receptive communication abilities. Conclusions: These findings indicate good tolerability of ERP procedures (85% success rate). The lack of own name differentiation is consistent with increased incidence of the autism‐related symptoms in AS. Strong associations between the caregiver reports of adaptive functioning and neural indices of known name recognition support the utility of brain‐based measures for objectively evaluating cognitive and affective processes in nonverbal persons with neurodevelopmental disorders.